An eco-social model in the development of curriculum and course contents in social work - Belchior-Rocha, H.; Ferreira, J. (INTED2018 Proceedings, 2018)
This paper aims to present the experience in the three levels of social work education at a public university where the Bachelor level is built in community context, the Master level in family context and the PhD studies in interdisciplinary research context. In all three levels theoretical education and practical skills in the training and qualification of social workers are focusing on sustainability, ecology, environment and ecosystemic theory, including the conceptualization of personal welfare and human rights. Social work establishes a strong link with the environment and sustainable development, as a profession and as an academic discipline. Bringing ecological issues and concerns into the vison of students and professionals gives the opportunity to promote a network of studies, systematize recommendations, and develop theoretical and scientific frames to support the practice. Thinking about challenges and opportunities of this century, social work as a profession needs to respond to current social issues such as a European social model under debate; a new paradigm of society identified with social citizenship; a cultural and ethnic diversity with challenges posed in the field of democracy and citizenship; globalization and the impact on the social well-being and quality of life; promotion of International Social Work; new and more complex social needs; evolution of new technologies and the information society. This study is essentially descriptive in nature though it has both quantitative and qualitative elements (mix methods). The focus of the “Ecosocial Model” on human rights, social justice and ethical values creates a solid foundation to reinforce the social work curricula. Therefore, Social Work education has an important role in bringing ecological issues and concerns into the vision of students and professionals. The practice along with research, in this area, gives also the opportunity to reflect, innovate and promote a global responsible citizenship. The results show that in social work practice, applying an ecological approach can be best understood as looking at persons, families, cultures, communities, and policies and to identify and intervene upon strengths and weaknesses in the transactional processes between these systems to generate transformation in social and human development, leading to an effective and sustainable change. Furthermore, it is an opportunity for aligning theoretical knowledge and learning, with the needs of society and the market place. It also affords students to take responsibility for addressing people’s problems. Therefore, becomes an important tool in bringing about a social work curriculum that is appropriate and responsive to sustainable social development issues.